PENYULUHAN PERUBAHAN PEMAHAMAN DALAM PENCEGAHAN DAN PENURUNAN STUNTING DI KECAMATAN BATUJAYA KARAWANG - Siti Nurhidayah; Hasan Basri; Ridwan Ridwan; Puput Putrianika; Dian Desty Widyowati; Ummi Khoiriyah (DEVOSI, 2023)
Stunting is a nutritional problem in the world, especially in developing and poor countries. Stunting can increase the risk of morbidity and mortality, as well as suboptimal brain development resulting in stunted motor development and mental retardation. Karawang Regency is one of 100 areas in West Java that is prioritized for stunting prevention. Based on the latest data released by the Karawang Regency Health Office, the results of the August 2020 Toddler Month Weighing were as many as 155,670 toddlers whose length and height were measured, the results obtained were 688 toddlers with very low nutritional status (0.4%) and 3,720 short toddlers (2.4%) ). Meanwhile, the normal height was 150,875 toddlers (96.9%) and the height was 387 toddlers (0.2%). The cause of the high stunting rate in Karawang Regency is very complex. The determinants of stunting cases that have been collected by the Karawang District Health Office are the lack of clean water, healthy latrines, immunization, the number of pregnant women who experience a lack of protein energy, the number of family members who smoke, children who have worms and families who do not have health insurance. Based on the identification of the problem of stunting in Karawang Regency, stunting is not hereditary so it can be prevented. The main factor is changes in people's behavior. Therefore, the Institute for Research & Community Service (LPPM Unisma) carries out community service activities by making outreach activities for changes in understanding in accelerating stunting prevention in Batujaya District, Karawang Regency. Activities to increase behavior change in accelerating stunting prevention in Batujaya District, Karawang Regency are actually only carried out in the form of counseling and psychoeducation regarding changes in understanding in accelerating stunting prevention by involving various parties so that they can have a positive impact. has an impact on preventing and reducing stunting, as well as providing basic food packages for vulnerable families.